Perbedaan Prestasi Akademik Mahasiswa Menurut Status Pekerjaan - Veti Melia Sari; Khusaini Khusaini; Aniek Widiarti (SAP (Susunan Artikel Pendidikan), 2023)
Academic achievement is one of the important indicators in measuring learning success from a cognitive aspect. Academic achievement will determine future students’ paths both to continuing to a higher level of education and competing in the job market. This study aims to examine differences in academic achievement, time management, learning motivation, and gender according to student employment status. The author also examines the impact of time management, employment status, and gender on student academic achievement. The population used 370 FKIP students at the Shekh-Yusuf Islamic University at Tangerang, Academic Year 2021/2022. The sample size was 192 students (5% sampling error) with purposive sampling technique. Data collection utilized an online questionnaire with a Google form which was distributed via WhatsApp. Data analysis utilized the Mann-Whitney U Test non-parametric difference test. The results of the study discovered that there were significant differences in student academic achievement based on the characteristics of job status, as well as differences in gender. The results of the binary logistic regression test found that gender had a significant effect, while time management and employment status did not. These findings contribute to increasing knowledge in the world of education, especially academic achievement. The existence of a student's employment status can have implications for the high and low academic achievement obtained.